REBOZO TECHNIQUE SHORTENS FIRST STAGE OF LABOR - Erma Nur Fauziandari; Amri Wulandari; Saumi Fijriyah; Lutfi Annarahayu (Universitas STRADA Indonesia, 2025)
The maternal mortality rate that occurs in maternal mothers in Indonesia reaches 189 per 100 thousand live births. 80% percent of maternal deaths are caused by direct factors, one of which is stuck Labor. One of the efforts to reduce the incidence of Labor jams is to shorten or speed up the length of labor. Efforts to speed up the duration of delivery in the first period is by managing the rebozo technique. Type of experimental research with case control design and sampling technique purposive sampling. The samples of 18 maternity mothers was divided into 2 groups, 9 in rebozo technique and 9 in control group. The results of the study, the analysis with an independent t test, obtained ρ value 0.018 < sig 0.005. From these results, it can be concluded that the rebozo technique is effective in shortening the length of delivery time during First Stage Labor.